Lipocalin 13 enhances insulin secretion but is dispensable for systemic metabolic control - Bühler, Lea; Maida, Adriano; Vogl, Elena Sophie; Georgiadi, Anastasia; Takacs, Andrea; Kluth, Oliver; Schürmann, Annette; Feuchtinger, Annette; Toerne, Christine von; Tsokanos, Foivos-Filippos; Klepac, Katarina; Wolff, Gretchen; et al. (Life science alliance, 2021)
Members of the lipocalin protein family serve as biomarkers for kidney disease and acute phase inflammatory reactions, and are under preclinical development for the diagnosis and therapy of allergies. However, none of the lipocalin family members has made the step into clinical development, mostly due to their complex biological activity and the lack of in-depth mechanistic knowledge. Here, we show that the hepatokine lipocalin 13 (LCN13) triggers glucose-dependent insulin secretion and cell proliferation of primary mouse islets. However, inhibition of endogenous LCN13 expression in lean mice did not alter glucose and lipid homeostasis. Enhanced hepatic secretion of LCN13 in either diet-induced or genetic obesity led to no discernible impact on systemic glucose and lipid metabolism, neither in preventive nor therapeutic setting. Of note, loss or forced LCN13 hepatic secretion did not trigger any compensatory regulation of related lipocalin family members. Together, these data are in stark contrast to the suggested gluco-regulatory and therapeutic role of LCN13 in obesity, and imply complex regulatory steps in LCN13 biology at the organismic level mitigating its principal insulinotropic effects.
Gesehen am 29.06.2021